Transmission Expansion for Renewable Energy Scale-Up : Emerging Lessons and Recommendations - Madrigal, Marcelino; Stoft, Steven (Washington, DC: World Bank, 2012)
Scaling up renewable energy, such as wind and solar, goes hand-in-hand with the expansion of transmission infrastructure. The richest solar and wind renewable energy sites are often located far away from consumption centers or existing transmission networks. Unlike fossil fuel-based power sources, renewable energy sources are greatly site-constrained and, for this reason, transmission networks need to be expanded to reach the renewable energy sites. Delivering transmission is a challenge, given the dispersion and granularity of renewable sources. Tapping a few hundred megawatts of renewable energy sources, such as wind and solar power, will likely require delivering transmission to several sites. Furthermore, transmission is also required to smooth out the variability of new renewable sources in a large geographical area. For these reasons, countries' renewable energy scale-up efforts are being challenged by the need for timely and efficient delivery of transmission networks. The objective of this report is to present emerging lessons and recommendations on approaches to efficiently and effectively expand transmission networks for renewable energy scale-up. The report focuses on the planning and regulatory aspects of transmission expansion that are relevant to transmission utilities and electricity regulators.